2004
DOI: 10.1242/jeb.00946
|View full text |Cite
|
Sign up to set email alerts
|

Navigation and seasonal migratory orientation in juvenile sea turtles

Abstract: Juvenile loggerhead and green turtles that inhabit inshore waters of North Carolina, USA undertake long seasonal migrations, after which they often return to specific feeding areas. In addition, juvenile turtles are capable of homing to specific sites after being displaced. As a first step towards investigating the navigational mechanisms that underlie these movements, juvenile turtles were captured in coastal waters of North Carolina and displaced 30-167·km along circuitous routes while deprived of visual cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 38 publications
1
23
0
1
Order By: Relevance
“…Thus, the turtles used in our experiments probably included individuals motivated to move toward different seasonally appropriate destinations rather than toward a single goal. Recent experiments have confirmed that the orientation behavior of juvenile turtles tested in arenas does indeed change seasonally; turtles tested during summer oriented toward the locations where they were captured (presumably in an effort to return to their feeding areas), whereas turtles captured during the autumn migratory season swam predominantly southward (Avens, 2003; L. Avens and K. J. Lohmann, manuscript in preparation).…”
Section: Orientation and Homing Behaviourmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, the turtles used in our experiments probably included individuals motivated to move toward different seasonally appropriate destinations rather than toward a single goal. Recent experiments have confirmed that the orientation behavior of juvenile turtles tested in arenas does indeed change seasonally; turtles tested during summer oriented toward the locations where they were captured (presumably in an effort to return to their feeding areas), whereas turtles captured during the autumn migratory season swam predominantly southward (Avens, 2003; L. Avens and K. J. Lohmann, manuscript in preparation).…”
Section: Orientation and Homing Behaviourmentioning
confidence: 88%
“…Under many circumstances, juvenile turtles displaced from their feeding grounds return to the areas where they were captured (Ireland, 1980;Musick and Limpus, 1997;Avens et al, 2003). Analyses of the directional headings of the 10 groups of turtles during their Day 1 trials suggested that many turtles attempted to home while tethered in the arena.…”
Section: Orientation and Homing Behaviourmentioning
confidence: 99%
“…Animals may transit be tween foraging areas depending on factors such as variations in current intensity, water temperature and food availability (Musick & Limpus 1997, Bass et al 2006). Avens & Lohmann (2004) studied displacements of juvenile green turtles in North Carolina, and reported that animals presented seasonal movements in order to stay in warmer waters. This behavior has also been observed in green turtles tagged in Uru guay, which display a pattern of in habiting lower latitudes in Brazil during colder periods (López-Mendilaharsu et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Such turtles often show fidelity to specific foraging areas, returning to them reliably after long, seasonal migrations or experimental displacements (Ireland, 1980;Avens et al, 2003;Avens and Lohmann, 2004). How the turtles return to these foraging areas was investigated using juvenile green turtles Chelonia mydas captured in their feeding grounds near the central east coast of Florida.…”
Section: Magnetic Maps and Target Areasmentioning
confidence: 99%